Basic aspects of phase changes under high pressure - Delgado, Antonio; Kulisiewicz, Leszek; Rauh, Cornelia; Benning, Rainer (Annals of the New York Academy of Sciences, 2010)
Some substances of technological importance reveal phase change phenomena in the pressure and temperature range typically applied in biotechnology and food processing. For example, media with high molar volumes like edible oils and fats undergo liquid-solid phase transition at pressure increases up to several hundred megapascals. This article is concerned with theoretical considerations of the line of coexistence of solid and liquid phases in the pressure and temperature domain that corresponds to the phase boundary as a function of temperature and pressure. A universal model equation based on the equilibrium thermodynamics allowing prediction of the phase transition line of homogeneous media with high molar volume is presented. Approximate solutions of the model equation are discussed, which allow the phase boundary of substances with high molar volume to be described by a linear relation at least sequentially. The methods of experimental determination of the phase boundary under high pressure are presented and an attempt is made to validate the theoretical model with respect to the experimental data. © 2010 New York Academy of Sciences.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.basica
Keywords: Edible oils; High pressure; Phase boundary; Phase change; Thermodynamic modeling

Beobachtung des Stofftransports ausgewählter Fluide in überkritischem Kohlendioxid - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.beobac

Bioaffinitätsanreicherung zum Nachweis von Staphylococcus aureus und Bacillus cereus in Milchprodukten. - Benning, Rainer; Delgado, Antonio (Food-Lab, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.bioaff

Cognitive and hybrid approaches as means for process optimisation - Benning, Rainer; Forstner, Judith; Procelewska, Joanna; Luschmann, Christian; Delgado, Antonio (Food Manufacturing Efficiency, 2010)
UnivIS-Import:2015-04-14:Pub.2010.tech.ITC.stmmec.cognit

Detection of foreign bodies in closed food containers supported with fluid-solid-interaction analysis - schmidt, Tobias R. H.; Osorio Nesme, Anuhar; Forstner, Judith; Beronov, Kamen; Benning, Rainer; Delgado, Antonio (American Society of Mechanical Engineers, Pressure Vessels and Piping Division (Publication) PVP, 2010)
UnivIS-Import:2017-12-18:Pub.2010.tech.ITC.stmmec.detect

Detektion und Klassifizierung von Oberflächenrissen während des Ausrollprozesses viskoelastischer Weizenteige durch online-fähige Bildverarbeitung - Turda, Anamaria; Mahadevappa, Jyothi; Groß, Frauke; Schick, Julia; von Bargen, Markus; Benning, Rainer; Lösche, Klaus; Delgado, Antonio (Proceedings der 20. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.detekt

Development of an inline measurement technique to assess the quality of wheat dough during the sheeting process - Mahadevappa, Jyothi; Groß, Frauke; Benning, Rainer; Delgado, Antonio (Journal of Cereal Science, 2015)
Dough sheeting is an important processing operation in the production of various bakery products. The surface cracks on laminated wheat dough are undesirable and generally affect the final quality of the baked products. Although approaches exist for crack detection in the food industry, there is still a need to transfer and adapt it to the desired application especially with respect to inline measurement in the baking field such as dough sheeting. Therefore, the objective of the proposed methodology is to design and develop an inline measurement technique capable of automatic detection and evaluation of the dough surface as well as its measurement in terms of crack ratio. By adapting this technique, different types of dough were tested for their sensitivity to different rolling steps which in turn provides the initial rolling behavior inferences of different dough varieties. The proposed algorithm for the detection of surface cracks is evaluated with various performance measures. Industrial relevance The work described in this research is a novel and innovative approach that offers to benefit manufacturers of sheeting equipment in the improvement of equipment design. The bakers owning small and medium-sized enterprises are specially privileged from the successful application of this study, because their competitive capability increases due to the possibility of cost reduction.
UnivIS-Import:2015-10-26:Pub.2015.tech.ITC.stmmec.develo
Keywords: Wheat dough; Sheeting; Detection of surface cracks; Image processing; Crack ratio

Entwicklung eines Hybriden Identifizierungstools von Mikroorganismen mittels FTIR-Spektren - Kessler, Birgit; Benning, Rainer; Wenning, Maraike; Schmitt, Jürgen; Scherer, Siegfried; Delgado, Antonio (Chemie Ingenieur Technik, 2006)
UnivIS-Import:2015-03-09:Pub.2006.tech.ITC.stmmec.entwic

Entwicklung eines neuartigen Prozesses zur Trocknung von Pasta - Groß, Frauke; Benning, Rainer; Bindrich, Ute; Heinz, Volker; Delgado, Antonio (Der Lebensmittelbrief - Ernährung aktuell, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.entwic_9

Entwicklung und Implementierung eines Fuzzy-Systems zur Prozessregelung des Auswalzvorgangs von Weizenteigen - Mahadevappa, Jyothi; Groß, Frauke; Börsmann, Julia; von Bargen, Markus; Benning, Rainer; Lösche, Klaus; Delgado, Antonio (Proceedings der 21. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.entwic

Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Neukam, Johannes; Bielke, Thorsten; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Journal of Physics : Conference Series, 2011)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as better characterization of the process by quantitatively evaluating the important parameter - the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.masstr_3

Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Defect and Diffusion Forum, 2012)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as a better characterization of the process by quantitative evaluation of the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity in to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized. © (2012) Trans Tech Publications.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.masstr
Keywords: Diffusion coefficient; Microgravity; Shearing-interferometer; Supercritical carbon dioxide

Medizinverfahrenstechnik in der personalisierten Medizin: Hämodynamik von interkranialen Aneurysmen - Lopez Ramirez, Efrain; Delgado, Antonio; Benning, Rainer; Rauh, Cornelia; Münsch, Manuel; Ertunc, Özgür (Chemie Ingenieur Technik, 2010)
UnivIS-Import:2015-04-14:Pub.2010.tech.ITC.stmmec.medizi_6

Modeling the two-stage anaerobic digestion of domestic wastewater with the development of a monitoring application - Vega De Lille, Marisela Ix Chel; Forstner, Judith; Groß, Frauke; Benning, Rainer; Delgado, Antonio (BRAZ J CHEM ENG, 2016)
The IWA Anaerobic Digestion Model No. 1 (ADM1) was chosen to simulate a two-stage anaerobic digestion lab-scale plant treating domestic wastewater. Initially, the model was preliminary tested using synthetic wastewater. The simulation results were satisfactorily compared to NH4+ and chemical oxygen demand (COD) data for the first and second stages, respectively. A transformation method was then applied to estimate from the domestic wastewater composition the input variables to the ADM1. After proper calibration and further validation, the model was able to successfully predict the COD degradation from a varying influent, showing its practical applicability. Finally, a standalone application based on the validated model was developed to be used for monitoring purposes at the treatment plant. The developed application is suitable for direct implementation at a full-scale plant without the need of additional software or specialized assistanc
UnivIS-Import:2018-02-22:Pub.2016.tech.ITC.stmmec.modeli
Keywords: Mathematical modeling; Domestic wastewater; ADM1; Standalone application; Two-stage anaerobic digestion

MRT-referenzierte diffuse NIR-Spektroskopie zur Entwicklung einer neuartigen Prozessführungsstrategie - Groß, Frauke; Benning, Rainer; Bindrich, Ute; Heinz, Volker; Delgado, Antonio (Proceedings der 18. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.mrtref

Neuartige Multikontakt-Detektion zur automatischen Erkennung von partikulären, festen Fremdkörpern in abgefüllten Lebensmitteln - Kasprzyk, Andreas; Forstner, Judith; Benning, Rainer; Mauermann, Marc; Majschak, Jens-Peter; Delgado, Antonio (Der Lebensmittelbrief - Ernährung aktuell, 2010)
UnivIS-Import:2015-04-14:Pub.2009.tech.ITC.stmmec.neuart
Keywords: Fremdkörpererkennung Multikontakt-Detektion

Neues Verfahren zum schnellen Nachweis lebensmittelrelevanter Mikroorganismen. - Benning, Rainer; Delgado, Antonio (Rundschau für Fleischhygiene und Lebensmittelüberwachung, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.neuesv

Novel approach for detection of foreign particles in beverages - Forstner, Judith; Benning, Rainer; Procelewska, Joanna; Osorio Nesme, Anuhar; Mauermann, Marc; Hanke, Tilo; Majschak, Jens-Peter; Delgado, Antonio (BrewingScience, 2012)
Foreign particles in food and beverages constitute a serious problem to industry, due to company image and legal responsibility, and the consumer, whose health might be threatened. In this case random testing does not suffice and every container has to be individually tested for absence of such particles. Consequently, there is an urgent need for a reliable, fast and low cost system, which can be automated and which can be applied to filled and closed containers. The presented paper describes a system, which is based on rotatory movement of bottles. Due to their importance glass and PET bottles were used as examples for the approach, forcing particles like glass splinters to move to the wall. Multiple contacts of the particle upon the wall follow from this proceeding and are recorded by a piezo sensor. After processing the resulting signals allow the detection of glass particles with dimensions down to 1 mm x 1 mm x 1 mm in aqueous liquids, like water, beer, butter milk or orange juice. Besides the costs an advantage of the system lies in the characteristic that an optical access is not necessary, both with respect to the material of the bottle and the contained liquid.
UnivIS-Import:2015-04-14:Pub.2012.tech.ITC.stmmec.novela
Keywords: Bverages; Detection system; Food; Foreign particles; Multi contact; Piezo sensor

Novel process management for drying of pasta for increase in process efficiency and product quality - Groß, Frauke; Benning, Rainer; Bindrich, Ute; Heinz, Volker; Delgado, Antonio (Delegate Manual, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.novelp

Numerical simulation of a multi-contact detection technique for foreign particles in closed food containers - Osorio Nesme, Anuhar; schmidt, Tobias R. H.; Beronov, Kamen; Benning, Rainer; Forstner, Judith; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2009)
UnivIS-Import:2015-04-14:Pub.2009.tech.ITC.stmmec.numeri_94

Optical online measurement technique used for process control of the drying step during pasta production - Groß, Frauke; Benning, Rainer; Bindrich, Ute; Franke, Knut; Heinz, Volker; Delgado, Antonio (Procedia Food Science, 2011)
The presented paper concentrates on the development of a fuzzy system to control the drying process of pasta plates. The system adjusts drying temperature as well as humidity by including knowledge of experts or from research in setting up models of the actual process respectively product state. As a basis the research led to the development of an appropriate online measurement setup that was implemented in a climate test chamber. Here relevant product information like - in this case - moisture content, colour and surface temperature of the pasta right during the running process are obtained. These three selected parameters are measured by an optical non-invasive approach with fast data acquisition. In addition to gravimetric measurements for referencing the spectroscopic approach resulting in values of the water content of pasta, magnetic resonance imaging is used to gain information of the moisture distribution within the cross section of a pasta plate. In combination with further product characteristics the quality of the product is evaluated and used in a fuzzy logic system that determines a situative and adjusted control strategy by correlating the product state with the suitable drying parameters temperature and moisture in the dryer. Adjusting the drying process with respect to the current process respectively product state realises an individual optimisation and leads to a high product quality, less product losses (due to e.g. internal thermal stresses or unwanted colour changes) and an improved energy usage. (c) 2011 Published by Elsevier B.V. Selection and/or peer-review under responsibility of 11th International Congress on Engineering and Food (ICEF 11) Executive Committee.
UnivIS-Import:2018-09-05:Pub.2011.tech.ITC.stmmec.optica
Keywords: process optimisation; control; fuzzy logic; pasta; drying

Optimierung von Prozessketten der Fleischverarbeitung auf der Grundlage von Referenz-Petri-Netzen - Xie, Qian; Groß, Frauke; Benning, Rainer; Delgado, Antonio (Chemie Ingenieur Technik, 2012)

Study of mass transfer in supercritical carbon dioxide (SCCO2) using optical methods - Delgado, Antonio; Benning, Rainer; Ertunc, Özgür; Hu, Miao; Nercissian, Vanusch; Berger, M. (Heat and Mass Transfer, 2017)

Study of mass transfer in supercritical carbon dioxide (SCCO2) using optical methods - Hu, Miao; Benning, Rainer; Delgado, Antonio; Ertunc, Özgür; Nercissian, Vanusch; Berger, M. (Heat and Mass Transfer, 2017)
The purpose of this work is to design and develop a type of experiment setup that would enable the direct observation of steady diffusion process in situ. Two different optical methods - shadowgraph and shearing interferometry - were used for the first time to visualise and quantitatively analyse the diffusion around a droplet of organic substance in supercritical carbon dioxide (SCCO2) as well as in its direct vicinity. We constructed and tested a cylindrical high-pressure chamber and an experiment system with a high speed camera. The solute/solvent combination of DL-α-tocopherol/SCCO2 was applied using shadowgraph. The diffusion coefficients at temperatures of 40o C, 50o C and 60o C and pressures between 75 bar and 90 bar were calculated based on the displacement of the droplet contour in the captured images. The shearing interferometry with a Wollaston-prism was then applied not only for the combination of DL-α-tocopherol/SCCO2, but also for other substances in SCCO2, for example for a type of rose oil and lubricant oil as well as for acetone, benzene, toluene and naphthalene. The changes of the refractive index gradient were directly measured and evaluated with the interferograms; afterwards changes of the density gradients and the diffusion coefficients were determined. We propose then a multivariate regression model to capture the relationship between the diffusion coefficient, the pressure and the temperature. To minimize the influence of gravity-driven convections in the solvent during diffusion, the experiments were also carried out under microgravity condition, i.e. in two parabolic flight campaign
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.studyo

Thermodynamisches Modell zum Fest/flüssig-Phasenübergang von Substanzen hohen molaren Volumens - Delgado, Antonio; Rauh, Cornelia; Benning, Rainer (Chemie Ingenieur Technik, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.ITC.stmmec.thermo

Towards system theory based adaptive strategies for high pressure bioprocesses - Delgado, Antonio; Baars, Albert; Kowalczyk, Wojciech; Benning, Rainer; Kitsubun, Panit (High Pressure Research, 2007)
High pressure has been shown to offer unique possibilities for designing novel bioprocesses and generating new structures. However, high pressure processes have to be considered also as instantaneous but not homogeneous. As a consequence of this, thermofluiddynamical processes influence molecular and cellular mechanisms and kinetics. Thus, the urgent requirement for creating an adaptive process management, missing in the literature, is obvious. In this paper, a first attempt towards the development of adaptive process strategies is presented. It is shown that adaptive strategies have to include considerations regarding the interactions of all the components of the high-pressure system, variances due to the biological origin of the substances, and, particularly, methods for managing different data and knowledge sources. Furthermore, suggestions for the suitable design of adaptive process management strategies are presented and discussed. By means of a few examples it is elucidated that hybrid methods can contribute significantly in achieving the adaptability required. This paper is conceived as a brief composition to a plenary lecture presented at the XLIV EHPRG Meeting 2006 in Prague.
UnivIS-Import:2015-04-14:Pub.2007.tech.ITC.stmmec.toward
Keywords: Adaptive strategies; Bioprocesses; Biosystems; Food; Heterogeneities; High pressure; Hybrid methods

Untersuchungen zum Stofftransport ausgewählter Substanzen in überkritischem Kohlendioxid mittels Shearing-Intereferometrie - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Bielke, Thorsten; Delgado, Antonio; Neukam, Johannes; Nercissian, Vanusch; Berger, Andreas (Proceedings der 19. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.unters

Vibrationsanalyse zur Zustandserkennung von Gütern in der Lebensmittelindustrie - Benning, Rainer; Forstner, Judith; Hu, Miao; Groß, Frauke; Mauermann, Marc; Majschak, Jens-Peter; Franke, Sven; Vogelpohl, Heinrich; Delgado, Antonio (VVD 2009 Tagung Verarbeitung und Verpackungstechnik "Zukunft gestalten", 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.vibrat